Evaluation of Neurotoxicity With Human Pluripotent Stem Cell–Derived Cerebral Organoids. Issue 4 (17th April 2023) - Parmentier, Thomas; LaMarre, Jonathan; Lalonde, Jasmin
Abstract: The recent development of human cerebral organoids provides an invaluable in vitro model of human brain development to assess the toxicity of natural or man‐made toxic substances. By recapitulating key aspects of early human neurodevelopment, investigators can evaluate with this three‐dimensional (3D) model the effect of certain compounds on the formation of neuronal networks and their electrophysiological properties with more physiological relevance than neurons grown in monolayers and in cultures composed of a unique cell type. This promising potential has contributed to the development of a large number of diverse protocols to generate human cerebral organoids, making interlaboratory comparisons of results difficult. Based on a previously published protocol to generate human cortical organoids (herein called cerebral organoids), we detail several approaches to evaluate the effect of chemicals on neurogenesis, apoptosis, and neuronal function when exogenously applied to cultured specimens. Here, we take as an example 4‐aminopyridine, a potassium channel blocker that modulates the activity of neurons and neurogenesis, and describe a simple and cost‐effective way to test the impact of this agent on cerebral organoids derived from human induced pluripotent stem cells. We also provide tested protocols to evaluate neurogenesis in cerebral organoids with ethynyl deoxyuridine labeling and neuronal activity with live calcium imaging and microelectrode arrays. Together, these protocols should facilitate the implementation of cerebral organoid technologies in laboratories wishing to evaluate the effects of specific compounds or conditions on the development and function of human neurons with only basic cell culture equipment. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Generation of human cerebral organoids from pluripotent stem cells Support Protocol 1 : Human pluripotent stem cell culture Basic Protocol 2 : Evaluation of neurogenesis in cerebral organoids with ethynyl deoxyuridine labeling Basic Protocol 3 : Calcium imaging in cerebral organoids Basic Protocol 4 : Electrophysiological evaluation of cerebral organoids with microelectrode arrays Support Protocol 2 : Immunostaining of cerebral organoids